Mitochondrial and lysosomal dysfunction in the pathogenesis of Parkinson’s disease - Schapira, Anthony (Henry Stewart Talks, 2014)
Pathogenesis of Parkinson’s disease (PD), Mitochondria (biochemistry, DNA, proteins, turnover), Oxidative phosphorylation and respiratory chain, Fraction of deleted mtDNA in substantia nigra (SN), Mitochondrial complex I deficiency in PD, PARK loci, The role of mitophagy in mitochondrial turnover, Common pathways underlying PD pathogenesis, Ageing and PD pathogenesis, Autosomal mitochondrial diseases, POLG mutations, Alpha-synuclein (SNCA) and mitochondria, Autophagy, lysosomal dysfunction and Glucocerebrosidase (GCase), Gaucher disease, Chaperone-mediated autophagy: LAMP-2A, GBA mutations, DAT density and disease progression in PD, DaTScan in genetic PD, GCase-SNCA as a target for PD, GBA & GBA-SNCA pathway as targets for PD therapies